Impact of neo-adjuvant Sorafenib treatment on liver transplantation in HCC patients - a prospective, randomized, double-blind, phase III trial - Hoffmann, Katrin; Ganten, Tom M.; Gotthardt, Daniel; Radeleff, Boris; Karapanagiotou-Schenkel, Irini; Kalle, Christof von; Jäger, Dirk; Büchler, Markus W.; Schemmer, Peter (BMC cancer, 2015)
Background: Liver Transplantation (LT) is treatment of choice for patients with hepatocellular carcinoma (HCC) within MILAN Criteria. Tumour progression and subsequent dropout from waiting list have significant impact on the survival. Transarterial chemoembolization (TACE) controls tumour growth in the treated HCC nodule, however, the risk of tumour development in the untreated liver is increased by simultaneous release of neo-angiogenic factors. Due to its anti-angiogenic effects, Sorafenib delays the progression of HCC. Aim of this study was to determine whether combination of TACE and Sorafenib improves tumour control in HCC patients on waiting list for LT. Methods: Fifty patients were randomly assigned on a 1:1 ratio in double-blinded fashion at four centers in Germany and treated with TACE plus either Sorafenib (n = 24) or placebo (n = 26). The end of treatment was development of progressive disease according to mRECIST criteria or LT. The primary endpoint of the trial was the Time-to-Progression (TTP). Other efficacy endpoints were Tumour Response, Progression-free Survival (PFS), and Time-to-LT (TTLT). Results: The median time of treatment was 125 days with Sorafenib and 171 days with the placebo. Fourteen patients (seven from each group) developed tumour progression during the course of the study period. The Hazard Ratio of TTP was 1.106 (95% CI: 0.387, 3.162). The results of the Objective Response Rate, Disease Control Rate, PFS, and TTLT were comparable in both groups. The incidence of AEs was comparable in the placebo group (n = 23, 92%) and in the Sorafenib group (n = 23, 96%). Twelve patients (50%) on Sorafenib and four patients (16%) on placebo experienced severe treatment-related AEs. Conclusion: The TTP is similar after neo-adjuvant treatment with TACE and Sorafenib before LT compared to TACE and placebo. The Tumour Response, PFS, and TTLT were comparable. The safety profile of the Sorafenib group was similar to that of the placebo group.Trial registration ISRCTN24081794
Daniel Gotthardtp falsch geschrieben, richtig: Daniel Gotthardt
Gesehen am 01.08.2017